2003
DOI: 10.1016/s0895-4356(03)00129-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting survival after treatment for fracture of the proximal femur and the effect of delays to surgery

Abstract: Background and Objectives: The aim of this study was to evaluate the prognosis after treatment for femoral neck fracture, to assess the impact of delay to surgery, and to devise a clinical prediction rule and score. Methods: A prospective observational study was conducted in which 1780 patients treated surgically in two teaching hospitals between 1 November 1997 and 31 October 1999 were followed over 12 months. Logistic regression was used to distinguish the effects of predictor variables on survival. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
3
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 22 publications
8
128
3
8
Order By: Relevance
“…Therefore, male gender, three or more comorbidities, Category III or IV ASA rating, and weaker prefracture ambulatory status predicted mortality. Similar results have been reported for patients without hemiplegia who have hip fractures [5,9,10,13,40]. In our preliminary analysis, age, type of fracture, prefracture ambulatory status, and side of fracture did not have an effect on recovery of prefracture ambulatory status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, male gender, three or more comorbidities, Category III or IV ASA rating, and weaker prefracture ambulatory status predicted mortality. Similar results have been reported for patients without hemiplegia who have hip fractures [5,9,10,13,40]. In our preliminary analysis, age, type of fracture, prefracture ambulatory status, and side of fracture did not have an effect on recovery of prefracture ambulatory status.…”
Section: Discussionsupporting
confidence: 89%
“…Various factors (eg, age [9,38], gender [10,13,38], ASA rating [9,17], dementia [4], and type of fracture [28,29]) reportedly affect ambulatory status and mortality of elderly patients with hip fractures, but little is known of any differences in general characteristics between patients with and without hemiplegia who had hip fractures, factors predicting recovery of prefracture ambulatory status, and mortality of patients with hemiplegia after stroke who experienced hip fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical delay after hip fractures has been studied extensively but continues to be a source of debate. Gdalevich et al [22] and Elliott et al [19] found surgical delay reduced the probability of 1-year survival. However, an effect of preexisting disease severity on mortality also was found.…”
Section: Discussionmentioning
confidence: 99%
“…Die 1-JahresMortalität nach einer Hüftfraktur liegt nach wie vor bei bis zu 30% [5]. Lediglich 50% der betroffenen Patienten erreichen wiederum ihren funktionellen Zustand vor dem Trauma [6].…”
Section: Alterstraumatologieneue Wege Neue Chancenunclassified